It's the occupation, stupid! Explaining candidates' success in low-information local elections - Mario Mechtel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We analyze the effects of personal characteristics of 4239 political candidates on their performance in local elections in Germany. Our results show that a candidate's occupation plays a decisive role. Occupational effects can be explained by (a) an occupation's public reputation and (b) public renownedness of individuals carrying out certain occupations. The findings regarding the occupational reputation effects are strongly correlated with polls on occupational reputation/prestige in the US and Germany.
Keywords: D72; D70; J01; 330; low-information elections; local elections; occupational reputation; political economy